Improves Vo2max: Hiit Vs Rst In Elite Players Of Persema Malang - Kirom, Muhammad Zayyin Agil; Pamungkas, Hari; Nidomuddin, Muhammad; Aofal, Reza; Agyanur, Shoffurijal (Jurnal Pendidikan Jasmani (JPJ), 2025)
High-intensity interval training (HIIT) and Repeated Sprint Training (RST) are very important for soccer performance, especially in maintaining high-intensity efforts throughout the match,. however, their effects on players remain unexplored, especially with regard to which maximum aerobic capacity (VO2max) is better between the two methods. This study using an experimental research design pre-test posttest control group design, with 20 PERSEMA Malang players with a similar age range of 21 years. Group A was given HIIT Training and Group B RST Training, each group consisted of 10 samples research. The treatment was carried out for 6 weeks of training. The results of the study of the two groups between pretests and posttests showed that both groups had a significance of 0.00 which showed < P = 0.05, but the results of the ANOVA difference test showed that the value was 0.044 (> P = 0.05). This research can be concluded that there is a significant difference between pretest and posttest on HIIT and RST training methods in increasing VO2max of Persema Malang players